Flying Around in the Genome: Characterization of LINE-1 in Chiroptera - Wichman, Holly A. (Spec Publ Tex Tech Univ Mus, 2019)
L1s are transposable elements that move by a copy-and-paste mechanism that continuously increases their copy number in the genome, such that each genome has a record of the L1 history in that host lineage. They make up about 20% of the genomes of eutherian mammals and have played a major role in shaping genome evolution. Chiroptera has the lowest average genome size among mammalian orders and the only documented case of L1 extinction affecting an entire mammalian family. Herein, L1 activity and extinction are characterized in all families of the order Chiroptera using a method that enriches for the youngest lineages of L1s in the genome. In addition to the previously reported L1 extinction in Pteropodidae, L1 extinction was documented to occur in Mormoops blainvilli, but this event did not affect all species of Mormoopidae. Further, there was no evidence of concordance between the evolution of L1s and their chiropteran host. There were two L1 lineages present before the divergence of all extant bats. Both lineages are extinct in the Pteropodidae. One or the other L1 lineage is extinct in almost all bat families, but Taphozous melanopogon maintains active members of both. Most intriguingly, some families within the Rhinolophoidea retain one active L1 lineage whereas other families retain the other, creating a deep discontinuity between L1 phylogeny and chiropteran phylogeny. These results indicate that there have been numerous losses of active L1 lineages over the history of chiropteran evolution, but that all chiropteran families except Pteropodidae have retained L1 activity.